2008
DOI: 10.3141/2070-05
|View full text |Cite
|
Sign up to set email alerts
|

Properties of Concrete Containing Vitreous Calcium Aluminosilicate Pozzolan

Abstract: A laboratory study was done on the influence of vitreous calcium aluminosilicate (VCAS), a new pozzolanic mineral admixture, on the properties of fresh and hardened portland cement concrete. A relative comparison was done of the performance of concrete containing VCAS with that of concrete containing silica fume (SF), one of the widely used mineral admixtures. The addition of VCAS pozzolan increased the slump (improved consistency) of the mixtures, while the addition of SF decreased it. The VCAS pozzolan was f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 13 publications
(9 reference statements)
0
7
0
Order By: Relevance
“…The improvement in resistance to chloride penetration may be related to the refined pore structure of these concretes and their reduced electrical conductivity (Talbot et al 1995). This which was confirmed by many researchers (Ghrici et al 2006;Rukzon and Chindaprasirt 2009;Chindaprasirt et al 2007;Gastaldini et al 2007;Pourkhorshidi et al 2010;Ramezanianpour et al 2010;Hossain et al 2008;Rukzon and Chindaprasirt 2009;Chindaprasirt et al 2007;Gastaldini et al 2007), is due to the secondary pozzolanic reaction which contributes to make the microstructure of concrete denser. If a higher volume of scoria is added, much lower penetrability can be achieved.…”
Section: Rapid Chloride Penetrabilitymentioning
confidence: 56%
“…The improvement in resistance to chloride penetration may be related to the refined pore structure of these concretes and their reduced electrical conductivity (Talbot et al 1995). This which was confirmed by many researchers (Ghrici et al 2006;Rukzon and Chindaprasirt 2009;Chindaprasirt et al 2007;Gastaldini et al 2007;Pourkhorshidi et al 2010;Ramezanianpour et al 2010;Hossain et al 2008;Rukzon and Chindaprasirt 2009;Chindaprasirt et al 2007;Gastaldini et al 2007), is due to the secondary pozzolanic reaction which contributes to make the microstructure of concrete denser. If a higher volume of scoria is added, much lower penetrability can be achieved.…”
Section: Rapid Chloride Penetrabilitymentioning
confidence: 56%
“…Furthermore, it was observed that the addition of E-glass as a cement replacement improved durability characteristics of concrete such as resistance against sulfate attack and chloride penetration. Hossein et al (8), studied the fresh and hardened properties of the concrete mixture containing glass fiber particles. It was reported that utilization of this material as a cement replacement increased the workability of the fresh concrete mixtures (higher slump), increased the plastic shrinkage and also reduced chloride ion permeability.…”
Section: Introductionmentioning
confidence: 99%
“…Chen et al (2) studied the utilization of waste E-glass (the most commonly used type of fiber glass) as cement replacement material. In addition, a number of studies were also conducted on the utilization of vitreous calcium aluminosilicate (which is a commercially produced pozzolan made from by-products of fiber glass) as cement replacement material (3,4) or as a precursor for geopolymer production (5,6).…”
Section: Introductionmentioning
confidence: 99%